BIBLIOMETRIC ANALYSIS: GLOBAL RESEARCH TRENDS ON STUDENTS' EPISTEMIC BELIEFS IN EDUCATIONAL PROCESS IN THE LAST DECADE - Umar, Umar; Kadir, Abdul; Wajdi, Muhammad; Slamet, Agus; Fitrah, Muh.; Rafiuddin, Rafiuddin (Universitas Labuhanbatu, 2025)
Purpose – Student epistemology can be understood as an intrinsic aspect that influences student success in learning activities. Therefore, teachers need to innovate learning methods based on the level of understanding and needs of students in order to conduct and engage them in learning activities within the school environment.Methodology – The research aims to map the trend of research development related to student epistemic in the learning process based on the Scopus database. There are 890 metadata records of Scopus-indexed journal articles from the period 2013-2022, which are analyzed bibliometrically using the VOSviewer software to identify trends in student epistemic research.Findings – The study's results revealed that research publications related to student epistemic development from 2013 to 2022, with the highest Scopus index in 2022, comprised 184 articles (20.44%). Bibliometric mapping also shows that student epistemic research with the themes